2013
DOI: 10.1371/journal.pone.0056994
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Stroke after the Death of a Sibling: A Nationwide Follow-Up Study from Sweden

Abstract: BackgroundAlthough less studied than other types of familial losses, the loss of a sibling could be a potential trigger of stroke as it represents a stressful life event. We studied the association between loss of a sibling and fatal stroke up to 18 years since bereavement. Methodology/Principal FindingsWe conducted a follow-up study between 1981 and 2002, based on register data covering the total population of Swedes aged 40–69 years (n = 1,617,010). An increased risk of fatal stroke (1.31 CI: 1.05, 1.62) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 24 publications
6
33
0
Order By: Relevance
“…We included six studies: five cohort studies and one case‐crossover study . All studies were conducted in Europe or the USA (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included six studies: five cohort studies and one case‐crossover study . All studies were conducted in Europe or the USA (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…We included six studies: five cohort studies and one case‐crossover study . All studies were conducted in Europe or the USA (Table ). Five studies found that the loss of a first‐degree relative was associated with a 1.1‐ to 2.4‐fold higher risk of stroke .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rostila et al [22] showed that the death of a close one could lead to serious medical conditions and sometimes death. Bereavement is known to affect people who are related to the deceased and at times even those who are not related to the deceased (Mathews et al [23] and Nazarko[24] ).…”
Section: Introductionmentioning
confidence: 99%
“…Sibling bereavement is an experience with a very sparse literature and thus the consequences of losing a sibling are unclear. A series of Swedish national cohort studies revealed increased mortality of bereaved siblings when compared to non‐bereaved controls. These analyses, however, were restricted to adult sibling populations and did not examine outcomes other than death.…”
mentioning
confidence: 99%